Effects of permethrin on the ovary in Xiphophorus helleri (Pisces poeciliidae) - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2007)
In this study, the effects of permethrin on the ovary of swordtail fish (Xiphophorus helleri) were determined. The fish were exposed to 25, 50 and 100 mu g/L permethrin during 30 days. No evidence was found for any histopathological effect of permethrin on oogonium development in all groups. In contrast, 50 and 100 mu g/L permethrin inhibited the vitellogenic, maturing and mature oocytes in ovary tissue, and 100 mu g/L permethrin were more toxic to vitellogenic oocytes than could be explained by an atretic mechanism of the other groups. Permethrin also caused clear behavioral changes in swordtail fish. The significance of these observations for the application of oocyte dynamics to impact assessment in freshwater environment is discussed.
Keywords: synthetic pyrethroids; permethrin; ovary; oocyte; Xiphophorus helleri; TROUT ONCORHYNCHUS-MYKISS; CYPRINUS-CARPIO; PYRETHROID INSECTICIDES; LEBISTES-RETICULATUS; FOSSILIS BLOCH; ACUTE TOXICITY; FISH; DELTAMETHRIN; IMPACT; FASCIATUS